Analysis of Dengue Fever Incident in Kendari Based on People, Place and Time - La Ode Liaumin Azim; Agnes Mersatika Hartoyo; La Ode Ahmad Saktiansyah (Health Gate, 2026)
The number of dengue fever cases tends to increase every year, especially during the rainy season when the spread of this disease increases. This study was conducted to provide an overview of the endemicity and incidence of dengue fever based on human, place, and time variables in the working area of the Benu-Benua Community Health Center from April to June 2025. The study was conducted from May 20 to June 21, 2025. This study used a survey design with a descriptive observational approach. The approach used was exploratory descriptive, with the aim of systematically describing and explaining various facts and data from the investigation, so as to provide an accurate picture of the conditions in the field. The results of the study showed that the evaluation of the accuracy and completeness of surveillance at the Benu-Benua Community Health Center was accurate and complete. Dengue fever cases in weeks 14-24 appeared in weeks 15, 18, and 19 with a total of 1 case, while there were no dengue fever cases in the other weeks (0 cases). Dengue fever cases were found in the 10-14, 25-29, and 40-44 age groups, which had the same number of cases, namely 1 case. The male gender had the highest number of cases, while no DBD cases were found in females. The highest number of DBD cases was found in the Tipulu work area (2 cases), followed by Sodohoa (1 case), and no DBD cases were found in other work areas.